Evaluation of Vehicle Transportation Procedures on Board Crossing Ships at Ulee Lheue Port – Balohan, Aceh Province - Nurlaili Triwahyuni, Siti; Sutrisno, Slamet Prasetyo; Yulianto, Andri (IWTJ : International Water Transport Journal, 2023)
Ulee Lheue Crossing Port is one of the ports in Aceh Province, which serves the Ulee Lheue – Balohan , Ulee Lheue - Serapung, Ulee Lheue - Lamteng. The stability or balance of the ship is important for the safety and security of the ship. Vessels loaded with excessive vehicles and goods endanger service users. This study aims to: 1) Find out the suitability of vehicle transportation procedures and 2) Know the need for the number of fastening tools. The method of collecting data by direct means of spaciousness is by measuring the distance between vehicles, loading the conditions of vehicle placement. The analysis that will be used is guided by PM Number 115 of 2016 concerning Procedures for Transportation of Vehicles on Ships and PM Number 30 of 2016 concerning Vehicle Binding Obligations on Crossing Transport Ships. The results of the analysis show that: 1) The placement of vehicles on board the ship is not in accordance with applicable regulations 2) The suitability of the distance between the sides of the vehicle on board the ship is not in accordance with the applicable Regulations 3) There is no fastening on board the ship that is in the row of bow, middle, stern 4.) The fastening tools on the ulee Lheue – Balohan track boat were insufficient as analyzed. The advice given by the author is that it is necessary to socialize by related parties regarding the implementation of binding policies and transportation procedures contained in PM 115 of 2016 and PM 30 of 2016 To operators, service providers, and Port supervisory officers.